2019
DOI: 10.1186/s12896-019-0533-7
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide response on phytosterol in 9-hydroxyandrostenedione-producing strain of Mycobacterium sp. VKM Ac-1817D

Abstract: Background Aerobic side chain degradation of phytosterols by actinobacteria is the basis for the industrial production of androstane steroids which are the starting materials for the synthesis of steroid hormones. A native strain of Mycobacterium sp. VKM Ac-1817D effectively produces 9α-hydroxyandrost-4-ene-3,17-dione (9-OH-AD) from phytosterol, but also is capable of slow steroid core degradation. However, the set of the genes with products that are involved in phytoste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 73 publications
0
15
0
Order By: Relevance
“…Acyl-CoA synthetase FadD19 catalyzes the formation of the cholestanoate CoA-thioester [ 13 ] that is further oxidized to C-17-ketosteroids by three successive cycles of β-oxidation [ 4 , 14 ]. 9α-Hydroxylase (KshAB, consisting of KshA and KshB subunits) and 3-ketosteroid-∆ 1 -dehydrogenase (KstD) [ 15 , 16 ] are well-known as key enzymes of steroid core degradation whose cooperative action provides the ring B opening (Fig. 1 ).…”
Section: Introductionmentioning
confidence: 99%
“…Acyl-CoA synthetase FadD19 catalyzes the formation of the cholestanoate CoA-thioester [ 13 ] that is further oxidized to C-17-ketosteroids by three successive cycles of β-oxidation [ 4 , 14 ]. 9α-Hydroxylase (KshAB, consisting of KshA and KshB subunits) and 3-ketosteroid-∆ 1 -dehydrogenase (KstD) [ 15 , 16 ] are well-known as key enzymes of steroid core degradation whose cooperative action provides the ring B opening (Fig. 1 ).…”
Section: Introductionmentioning
confidence: 99%
“…The global transcriptome analysis of Mycobacterium sp . VKM Ac-1817D, a strain producing 9OH-AD and genetically close to NRRL B-3805, revealed that phytosterols stimulated the increased expression of 260 genes, including those related to steroid catabolism in mycobacteria [ 19 ]. Other bacteria contain either a similar steroid degradation pathway, e.g., in Pseudomonas sp.…”
Section: Introductionmentioning
confidence: 99%
“…The cells taken in the exponential growth phase (16 h) were harvested by centrifuge at 8000× g for 10 min. mRNA was isolated as described earlier [ 27 ]. The resulting mixture was treated with a Turbo DNA-free kit (Thermo Fisher Scientific, Whaltham, MA, USA).…”
Section: Methodsmentioning
confidence: 99%